Depression in Business: Herbal or Modern Medicine - Manikam, Lokanathan M.S (International Journal of Medical and Health Sciences Research, 2017)
The purpose of this study is to investigate the effectiveness of Hypericum for treating tensions in nowadays commonly business chaos. St. John’s Wort and Duloxetine, Cymbalta as both types of medicine are commonly used to treat depression in the business community today. It focused and covered on the possible side effects, chemical compound structure, functionality, background of both medicine. The previous scientific articles, research papers, case studies, patients’ reviews and issues regarding to the practice of these two medicines have been reviewed and taken into account as well. By identifying the previous clinical researches, St. John’s Wort is safe but less effective due to the unclear evidences. Duloxetine could be safe with presence of safety measures and effective with supporting clear evidences. St John’s Wort could only work as alternative medicine for business tensions unless an individual hardly tolerates with Duloxetine. The priority of Duloxetine hence is over St John’s Wort in choosing medicine for depression treatment as Duloxetine could be safe and more effective than St John’s Wort. By looking at various perspective of both type of medicine provided based on supportive evidences, it concluded that Duloxetine was more reliable and effective than St. John’s Wort in treating depression in our modern business community.